Individuality and Shareability: An Exploration to the Nishida Kitaro’s Account of the Absolute Negation-qua-Affirmation - Djunatan, Stefanus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2011)
The internal justification of the individuality leads us to a tendency of a solipsistic self. This justification lacks a consideration to include external agent or the others as a part of recognition of the individuality of the self. The analytical approach argues that the reference of the external agent in utterance realizes the individuality of the speaking subject. This viewpoint of the significance of the external agent should be equipped with another approach. Nishida’s account of the principle of the absolute negation qua affirmation brings forth the argument that the individuality of the self realizes the nature of interconnectivity with the others. This interconnectivity then marks the shareability of individuals. This article yearns for a social system that allows the safeguarding of the individual and at once the upgrading of dialogical interactions between individuals for the benefit of ingenious construction of the world of reality. Keywords:*internal justification *solipsistic self *individuality *shareability *absolute negation qua affirmation *shareability of the self *continuity of discontinuity *public place *dialogical interactions